Outline of therapeutic interventions with muscarinic receptor-mediated transmission - Jakubík, J; Šantrůčková, E; Randáková, A; Janíčková, H; Zimčík, P; Rudajev, V; Michal, P; El-Fakahany, E E; Doležal, V (Physiological research, 2014)
Muscarinc receptor-mediated signaling takes part in many physiological functions ranging from complex higher nervous activity to vegetative responses. Specificity of action of the natural muscarinic agonist acetylcholine is effected by action on five muscarinic receptor subtypes with particular tissue and cellular localization, and coupling preference with different G-proteins and their signaling pathways. In addition to physiological roles it is also implicated in pathologic events like promotion of carcinoma cells growth, early pathogenesis of neurodegenerative diseases in the central nervous system like Alzheimer's disease and Parkinson's disease, schizophrenia, intoxications resulting in drug addiction, or overactive bladder in the periphery. All of these disturbances demonstrate involvement of specific muscarinic receptor subtypes and point to the importance to develop selective pharmacotherapeutic interventions. Because of the high homology of the orthosteric binding site of muscarinic receptor subtypes there is virtually no subtype selective agonist that binds to this site. Activation of specific receptor subtypes may be achieved by developing allosteric modulators of acetylcholine binding, since ectopic binding domains on the receptor are less conserved compared to the orthosteric site. Potentiation of the effects of acetylcholine by allosteric modulators would be beneficial in cases where acetylcholine release is reduced due to pathological conditions. When presynaptic function is severely compromised, the utilization of ectopic agonists can be a thinkable solution.
Keywords: Nervous System Diseases; signální transdukce; Neurons; Receptors, Muscarinic; Signal Transduction; Animals; Humans; Muscarinic Agonists; lidé; receptory muskarinové; zvířata; antagonisté muskarinových receptorů; neurony; agonisté muskarinových receptorů; nemoci nervového systému; Muscarinic Antagonists